Two new species of Dryophthorinae in the genera Metamasius and Melchus from the Lesser Antilles (Coleoptera: urculionidae) - Anderson, Robert S. (Zootaxa, 2013)
Metamasius planatus and Melchus jessae, are described and illustrated from the Lesser Antilles islands of Dominica and St. Lucia.  Metamasius planatus (Dominica) is distinguished by a relatively flat profile and presence of dense, very fine, golden micropilosity covering most of the dorsal surface.  Melchus jessae (Dominica and St. Lucia) is the sixth species known in the genus and is distinguished by the cylindrical rostrum (not laterally compressed apically).  Information on natural history for both species is limited: some Metamasius planatus and one Melchus jessae were collected in bases of Euterpe globosa fronds. A revised key to genera of Neotropical Litosomini is presented.